Política nacional de educação ambiental: a educação ambiental como meio de estratégia para construção de um futuro sustentável - Diógenes, Ana Flávia Monteiro (2024)
This research aimed to discuss the strengths and weaknesses of the National Policy of Environmental Education, implemented by Law 9,795/1999, recognizing its importance for the construction of a more environmentally conscious and committed society. To achieve this general objective, specific objectives included understanding the general aspects of environmental education, discussing the guiding principles of Environmental Law in the Brazilian legal system, and reflecting on the National Policy of Environmental Education Law from the perspective of strengthening popular participation. The adopted approach was deductive, starting from general constructions to specific aspects of the National Policy of Environmental Education, particularly its strengths and weaknesses. The procedure method was descriptive, exploring and describing issues related to environmental education. The research technique used was bibliographic review, seeking elements in doctrine, articles, legislation, and other sources to understand the phenomenon under study. Throughout the study, the importance of formal environmental education in building a more sustainable and conscious society was highlighted. It was recognized that environmental education promotes awareness, understanding of interactions between humans and the environment, and provides knowledge about ecosystems, biodiversity, and natural resources. Despite the advances provided by legislation, such as the mandatory nature of environmental education at all levels of education and teacher training, weaknesses compromising its effectiveness were identified. These include the lack of implementation of Environmental Law principles, the isolated approach to environmental education, and the lack of clear strategies for popular participation in environmental management. Therefore, measures such as promoting popular participation, integrating environmental themes transversally into school curricula, and continuous teacher training were proposed to strengthen environmental education in Brazil. It is concluded that continuous reflection on environmental education and seeking ways to make it more effective are necessary, thus ensuring the preparation of future generations to face current environmental challenges.